The Influence of Cognitive Strategies Towards Student Ability In Determine The Main Idea In Descriptive Text - Gumelar, Wahyu Satya; Khoerunnisa, Nadia Cinta (Universitas Nusantara PGRI Kediri, 2024)
This research aims to identify the influence of cognitive strategies toward student ability in determining the main idea in descriptive text. This research uses quantitative research methods, using the preexperiment method with the design of the one group pretest posttest. The researchers uses tests as a data collection technique, then pretest and posttest as research instruments. Participants in this research were 52 class XI students of SMK 2 LPPM RI Majalaya. Research data shows that cognitive strategies help students in determine the main idea in descriptive text. Students can demonstrate better reading comprehension skills. This data is supported by the pretest results which have a mean value of 52.02 and posttest results which have a mean value of 87.92. Furthermore, the results of hypothesis test using paired sample t-test method show that there is a significant influence of the use of cognitive strategies toward students ability to determine the main idea in descriptive text with the Sig value. < 0.05 or 0.001 < 0.05. Based on the research results, cognitive strategies influence students ability in determine the main idea in descriptive text.